2002
DOI: 10.1002/1099-0682(200203)2002:3<639::aid-ejic639>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Functionalization of Vinylic C−F Bonds by Transition Metal Compounds: The Factors Determining Reactions between Nucleophiles and a (Perfluorovinyl)diiron(I) Complex; Syntheses of Diiron Derivatives Containing New C−N, C−S, C−H and C−O Bonds

Abstract: The reactions between alcohols ROH (R = Me, Et) and RR(OH)2 (RR = CH2−CH2) and the [perfluoro(sulfanyl)vinyl]diiron complex [{Fe(CO)3}2{µ‐C(SMe)(CF3)CβCαF2}] (1) in THF at room temperature involve substitution at the Cα atom to give new (alkoxymethylene)thiaferracyclobutadiene compounds [{Fe(CO)3}2{µ‐S(Me)C(CF3)CβCα(OR)2}] [R = Me (2a), Et (2b); RR = CH2CH2 (2c)]. Treatment of 1 with aniline and (methoxycarbonyl)hydrazine, bases of intermediate strength according to Pearson, produces α,β‐substituted thiaferrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…1 Numerous works in the literature focused on the construction of carbon−carbon 2 or carbon−heteroatom bonds (e.g., C−N, 3 C−O, 4 and C−S 5 ) via direct C−H activation, employing nucleophiles, such as organometallics, 6 alcohols, 7 carboxylates, 8 hydrazoates, 9 and amides, 10 as coupling partners.…”
Section: ■ Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…1 Numerous works in the literature focused on the construction of carbon−carbon 2 or carbon−heteroatom bonds (e.g., C−N, 3 C−O, 4 and C−S 5 ) via direct C−H activation, employing nucleophiles, such as organometallics, 6 alcohols, 7 carboxylates, 8 hydrazoates, 9 and amides, 10 as coupling partners.…”
Section: ■ Introductionmentioning
confidence: 72%
“…As environmental and atom-economical advantages, transitionmetal-catalyzed C−H activation has been widely used as a versatile synthetic methodology, with important applications to functionalizing hydrocarbons. 1 Numerous works in the literature focused on the construction of carbon−carbon 2 or carbon−heteroatom bonds (e.g., C−N, 3 C−O, 4 and C−S 5 ) via direct C−H activation, employing nucleophiles, such as organometallics, 6 alcohols, 7 carboxylates, 8 hydrazoates, 9 and amides, 10 as coupling partners.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3). The trans-influence of imine N atom (N1) leads to shortening of Fe-P3 bond length (2.2279( 10 3 The molecular structure of 10 with 30% probability ellipsoids (all of the hydrogen atoms are omitted for clarity), selected bond distances (A ˚) and angles (deg): Fe-N1 1.970(3), Fe-C1 2.007(4), Fe-C16 2.031(4), Fe-P3 2.2279 (10), Fe-P2 2.2427 (11), Fe-P1 2.2465 (11), N1-C7 1.303(5), C7-C6 1.415(5); N1-Fe-C1 80.56(13), N1-Fe-C16 81.35(13), C1-Fe-C16 161.91 (15), N1-Fe-P3 174.17 (9), C1-Fe-P3 93.61 (11), C16-Fe-P3 104.48 (11), C16-Fe-P2 85.32 (10), C1-Fe-P1 93.39 (10), C16-Fe-P1 86.39 (10) (C24-N2 = 1.362(4) A ˚) and C13-N1 = 1.360(4) A ˚) in complex 11 are even longer than the aforementioned C N distances as a result of p-coodination of the C N bond, which significantly weakens the C N bond. Complex 11 has a C2 symmetry axis through the central iron atom.…”
Section: Reaction Of Fe(pme 3 ) 4 With 26-difluorophenylmethylidene N...mentioning
confidence: 99%
“…14 It has been confirmed that the perfluorovinyldiiron complex reacts readily with nucleophiles to give novel organometallic complexes through an unusual C-F bond cleavage process. 15 Holland reported the synthesis and reactivity of low-coordinate iron(II) fluoride with diketiminate iron(II) ligands. 16 It was found that direct reaction of fluorinated aromatics with iron(II) hydride complexes did not occur, but C-F bond activation became feasible in the presence of silane as a fluoride trap.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies since the reviews mentioned above should not be ignored. They focused on metal complexes of, e.g., Ti, 9 Zr, [10][11][12] Fe, 13 Ni, 14,15 Ru, 16,17 Rh, [18][19][20][21][22] Re, 23 Os, 24 Ir, 25,26 and Yb. 27 While not directly connected to carbon-fluorine bond activation, it appears that enzymes can be employed to form such bonds.…”
Section: Introductionmentioning
confidence: 99%